The Mix of Good Nutritional Attitude and Poor Nutritional Knowledge is Associated with Adequate Intake of Vitamin A and Iron from Wild Fruits and Vegetables among Rural Households in Acholi Subregion of Northern Uganda - Okidi, Lawrence; Odongo, Walter; Ongeng, Duncan (Food Science & Nutrition, 2018)
Nutritional knowledge and attitude of a population greatly affect intake of essential micronutrients. Much of the understanding on the impact of nutritional knowledge and attitude on nutrient intake has been derived from studies conducted among affluent societies using commercial food products. However, information on the link between status of nutritional knowledge and attitude on intake of essential nutrients from wild fruits and vegetables among rural communities is largely lacking. This study examined the status of nutritional knowledge and attitude associated with intake of vitamin A and iron from wild fruits and vegetables among rural households in Acholi subregion of northern Uganda. A cross-sectional study design making use of individual household questionnaire and proximate dietary recall of a calendar year consumption period involving 248 randomly selected rural households was applied. Results showed that households had good nutritional attitude but poor nutritional knowledge. Status of knowledge was dependent on nutrition training (p = 0.028; coefficient, β = 0.710) and age of the respondent (p = 0.044; β = −0.023), whereas status of attitude was predicted by age of the respondent (p = 0.014; β = 0.048). Consumption of wild fruits and vegetables contributed adequately to the dietary vitamin A and iron requirements of the households. The results have demonstrated that intake of vitamin A and iron from wild fruits and vegetables among rural households is associated with good nutritional attitude but poor nutritional knowledge. A concerted effort is necessary to improve household nutritional knowledge for better utilization of wild fruits and vegetables.
Keywords: attitude, iron, Knowledge, vitamin A, wild fruits and vegetables